PERANCANGAN ASET DESAIN 3 DIMENSI SEBAGAI PENDUKUNG KONTEN PROMOSI PENERIMAAN MAHASISWA BARU UNIVERSITAS INTERNASIONAL SEMEN INDONESIA TAHUN 2024 - Syahjihaan Nabiila Raharjo; Rizky Noviasri (Proceeding Maritime Business Management Conference, 2023)
Increasing the number of students preparing to continue their studies at tertiary institutions has caused public and private universities to compete in order to promote their campuses during the new student admissions period. One method that is commonly used is through digital promotional content to attract prospective superior students. Likewise, with the Universitas International Semen Indonesia, while being a relatively young private university, it is necessary to participate in promoting campus achievements and excellence through digital marketing promotional content which is an information medium that is currently popular in this era. The UISI marketing department realizes the need to always follow trends that are currently popular to attract the attention of prospective new students. With the increasing popularity of the 3D design style in the creative industries, this design style is expected to be able to support the visual quality of promotional content designed by UISI during the 2024 new student admission period. The research method of this thesis is qualitative research with narrative data presentation and refers to Branding design theory by Wheeler (2009) which consists of conducting research, clarifying strategy, designing identity, creating touchpoints, and managing assets. This research will help the marketing division of UISI to create exclusive assets that follow visual trends to gain highschoolers’ interests on UISI’s social media promotional content especially during the new student admissions.